2012
DOI: 10.2147/ijn.s26468
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated photothermal antitumor therapy with multidye nanoparticles

Abstract: Purpose: Photothermal therapy is an emerging cancer treatment paradigm which involves highly localized heating and killing of tumor cells, due to the presence of nanomaterials that can strongly absorb near-infrared (NIR) light. In addition to having deep penetration depths in tissue, NIR light is innocuous to normal cells. Little is known currently about the fate of nanomaterials post photothermal ablation and the implications thereof. The purpose of this investigation was to define the intratumoral fate of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
(25 reference statements)
1
2
1
Order By: Relevance
“…Our findings are in contrast to another study conducting fractionated PTT in mice which reported great response after four treatments using a laser intensity even lower than the one used in this study, although in smaller tumors 23. Hence, there are probably many factors that can contribute to the treatment outcome, such as choice of photothermal agent, tumor size at initiation of treatment, laser dose, and treatment protocol.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are in contrast to another study conducting fractionated PTT in mice which reported great response after four treatments using a laser intensity even lower than the one used in this study, although in smaller tumors 23. Hence, there are probably many factors that can contribute to the treatment outcome, such as choice of photothermal agent, tumor size at initiation of treatment, laser dose, and treatment protocol.…”
Section: Discussioncontrasting
confidence: 99%
“…One mouse in the four-treatment group even experienced complete tumor regression. The group sizes in this study were comparable to other studies on PTT and fractionated therapy 23,24. However, it should be noted that at these group sizes the risk of type II statistical errors make detection of smaller survival benefits difficult to show.…”
Section: Discussionsupporting
confidence: 78%
“…Another strategy is to give the treatment in low-dose fractions instead of a single dose, thereby killing cancer cells that survived during the first treatment in following treatments and avoiding surface overheating [ 163 , 164 , 165 ]. Simón et al applied a fractionated PTT, using silica–gold nanoshells (NS), instead of one-dose therapy to increase the efficacy of photothermal treatment of subcutaneous colon carcinoma tumors in mice [ 166 ].…”
Section: Other Strategies For Pain Management In Pttmentioning
confidence: 99%
“…Some additional nanomaterials used in conjunction with photothermal therapy include silicon nanowires with gold nanoparticles 65 ; CuS nanoparticles 66 - 69 ; multidye mesoporous silica with silane-conjugated heptamethine cyanine dye loaded with silicon 2,3-napthalocyanine dihydroxide dye 70 ; single walled carbon nanotubes 71 ; porous silicon nanoparticles 72 ; NIR resonant silica core, gold shell, PEG nanoparticles 73 ; chitosan-coated triangular silver nanoparticles 74 ; and palladium nanosheets 75 , 76 .…”
Section: Phototriggered Theranostics For Cancer Applicationsmentioning
confidence: 99%